Implementasi Metode Pareto Abc untuk Pengendalian Persediaan Obat di Apotek Zhafirah - Ronaldi Aprilianto; Juju Jumadi; Reno Supardi (Jurnal Komputer, Informasi dan Teknologi, 2024)
Apotek Zhafirah often experience difficulties in making decisions for drug procurement. This is due to a factor that must be considered by the dispensary manager, namely the number of sales of drug items. Pharmacy managers are required to find ways to control the right order so as to reduce the occurrence of drug accumulation. The system is designed by paying attention to user needs related to Pareto ABC analysis process, which is a method used for inventory planning analysis. The system implementation uses the Visual Basic 2010 programming language and the research method used in this research is the waterfall method. Waterfall method is able to analyze the needs used to find out from the weaknesses of the old system, then make a design and continue with the design of the new system. By using Pareto ABC method, the results showed that drug data from January to December 2022 for the type of drug acarbose 50Mg consisted of Group A (March, June, July, August, September), Group B (January, April, May October) and Group C (February, November, December) while the amount of procurement was 9,642.